Maintaining tree biodiversity in urban communities on the university campus - ARIDA SUSILOWATI; AHMAD BAIQUNI RANGKUTI; HENTI HENDALASTUTI RACHMAT; APRI HERI ISWANTO; MOEHAR MARAGHIY HARAHAP; DENI ELFIATI; BEJO SLAMET; IDA MALLIA GINTING (Society for Indonesian Biodiversity, 2021)
Abstract. Susilowati A, Rangkuti AB, Rachmat HH, Iswanto AH, Harahap MM, Elfiati D, Slamet B, Ginting IM. 2021. Maintaining tree biodiversity in urban communities on the university campus. Biodiversitas 22: 2839-2847. Many universities worldwide have green spaces (GS) as an integral part of their campuses because of significant benefits for ecological function and urban communities. University of Sumatera Utara (USU) campus is located in urban area of Medan city, Indonesia, with a total area of 120 hectares. The campus offers various outdoor spaces for resting, sports, playgrounds and other psychological benefits. The campus also offers vital benefits for its surrounding environment, such as improving air quality and ensuring pleasant climatic conditions and biodiversity. One of the important functions of USU GS is to become an area for preserving tree diversity in urban communities, which in busy urban communities is sometimes a little overlooked. This research aimed to identify the species diversity, abundance, utilization, and conservation status of trees across 120 hectares of USU Campus using the field inventory method. Results revealed a total of 7333 individual trees of 121 species from 37 families. The most common tree species is Swietenia macrophylla (18.37%), while the dominant families are Fabaceae. Margalef index and the Shannon-Wiener diversity index reaching 13.48 (good) and 3.41 (high). Based on the utilization status, 55.43% of the tree species were wood producers, 45.34% were pollutant absorbers, while the lowest percentage functioned as latex producers (0.12%). About 70 species (57.85%) were native species, while 51 species (42.15%) were exotic. According to the International Union for Conservation of Nature (IUCN), 50 species (41.33% %) were listed as the least concern status, 8 species (6.61%) with a vulnerable status, 4 species (3.30%) with a near-threatened status and 2 species (1.66%) with and endangered status. The result from this study also showed that GS at USU not only performed its main function as a shade or an oxygen producer (environment services) but also maintained the tree biodiversity and a means of ex-situ conservation for many trees species. Trees threatened by anthropogenic activities, particularly tree felling for infrastructural developments were still found in the campus area. Therefore, sustainable conservation efforts should be geared towards ensuring the continued existence of the trees to maintain their ecological functions